Impacto de la implementación de una farmacia satélite en el gasto por consumo de rocuronio y vecuronio en la sala de operaciones del hospital Víctor Lazarte Echegaray de Trujillo” - Paredes Basilio, Hilda Lizeht (2009)
This research is a descriptive study - a retrospective cross to determine the impact of the implementation of a satellite pharmacy in the consumption expenditure of rocuronium and vecuronium in the Operations Room of the Hospital Víctor Lazarte Echegaray Trujillo. Data for this research work of these non-depolarizing neuromuscular relaxants were obtained with the help of the Hospital Management System for the Office of Statistics and Informatics Hospital Víctor Lazarte Echegaray Trujillo in which all joined Sheets consumption, and planillones recipes textbooks prescribed Surgical Center - Operations Room of patients admitted to the Hospital Board of Trujillo Victor Lazarte Echegaray dispensed by Pharmacy Store and Pharmacy Operations Room before and after its implementation, respectively (March 2006 to December 2007). Data were collected in a data form developed for this research. The following results were obtained: In the period March to December 2006 there was a higher consumption of rocuronium bromide consumed 1865 units at a cost of s /. 45.28 per unit soles this means spending a s/.84, 447.2 for the hospital (before the implementation of the Pharmacy Board of Satellite Operations). In the period from March to December 2007 there was a consumption of 634 units, it must be emphasized that there were two acquisition costs for the reverse that was involved and the ES-SALUD and MINSA from March - June s/.26.59 and July from December a s/.18.25 each one making a total of 12,879.88 for the hospital, generating a savings s/.71,567.32 in 2007 after the implementation of the FARSOP. With respect to vecuronium bromide, the total units consumed during the period March to December 2006 were 4188 units at a cost of each unit s/.5.4 this represents a total expenditure of s/.22,615.2 for the hospital before the implementation of the FARSOP. In 2007 March-December period after the implementation of the FARSOP, units consumed were 1977 units, there were two prices for the purchase by reverse s /. 5.65 from March to June and from July to December s/5.95, representing a total cost of s /. 11,455.95 for the hospital, generating a savings of s /. 11,159.25 after the implementation of the FARSOP. In conclusion, it is clear that the consumption and cost of non-depolarizing neuromuscular relaxant in the Surgical Center Hospital Víctor Lazarte Echegaray has decreased significantly with the implementation of the Pharmacy Board of satellite operations, which allowed significant savings in that institution, and above all, a rational use of these relaxants.